Further evidence of POP1 mutations as the cause of anauxetic dysplasia. Issue 9 (6th July 2016) - Elalaoui, Siham Chafai; Laarabi, Fatima Zahra; Mansouri, Maria; Mrani, Nidal Alaoui; Nishimura, Gen; Sefiani, Abdelaziz
Abstract : Anauxetic dysplasia (AAD, OMIM 607095) is a rare skeletal dysplasia inherited as an autosomal recessive trait, which is caused by mutations in RMRP and allelic to a more common disorder, cartilage hair hypoplasia (CHH). CHH is a multi‐system disorder with a variety of extraskeletal changes. Whereas AAD is a bone‐restricted disorder with a more severe skeletal phenotype: affected individuals are extremely short and complicated by orthopedic morbidity, and the radiological changes include modification of the vertebral bodies and epiphyseal dysplasia of the hip, as well as generalized metaphyseal dysplasia and severe brachydactyly. Recently, genetic heterogeneity for AAD was proposed, because a familial case (two affected sibs) with an AAD‐identical phenotype had compound heterozygous mutations in POP1, encoding a molecule functionally related to the gene product of RMRP . We report here a 5‐year‐old boy with the same phenotype born to a consanguineous couple. We identified a novel homozygous POP1 mutation (c.1744C>T, p.P582S) in the boy and the heterozygosity in the parents. It may be rational to coin the POP1 ‐associated skeletal phenotype AAD type 2. © 2016 Wiley Periodicals, Inc.